Baltic and Finnic linguistic relations reflected in geolinguistic studies of the Baltic languages - Stafecka, Anna (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2014)
The article provides insight into the reflection of Baltic and Finnic language contacts in geolinguistic studies of the Baltic languages. These contacts have a rather long history, and are particularly intense between the Latvian language and Finnic languages (especially Livonian and Estonian). In Lithuanian, Finnic borrowings have mostly appeared through Latvian, and fall into the dialectal Lithuanian vocabulary. The analysed material makes it possible to distinguish several areas of Finnic influences in Latvian sub-dialects. They are as follows: 1) the territory of the Livonian dialect which originated from Latvian-Livonian contact; 2) the sub-dialects along the Estonian border; 3) the sub-dialects around Gulbene and Alūksne; 4) the territory of the krieviņi (descendants of people who spoke Votic) in the Zemgale region; and 5) the sub-dialects in the Latgale region around Ludza. Geolinguistic research on language contacts may be helpful in solving certain problems of ethnic history.Kokkuvõte. Anna Stafecka: Balti ja läänemeresoome keelesuhete kajastus balti keelte geolingvistilistes uurimustes. Artikkel esitab ülevaate balti ja läänemeresoome keelesuhete kajastamisest balti keelte geolingvistilistes uurimustes. Neil kontaktidel on küllaltki pikk ajalugu ja need on eriti tugevad läti ja läänemeresoome keelte (eriti liivi ja eesti keele) vahel. Leedu keelde on läänemeresoome laenud saadud peamiselt läti keele vahendusel ja need kuuluvad leedu murdesõnavarasse. Analüüsitud materjal võimaldab eristada Läti murrakutes mitut läänemeresoome mõjupiirkonda: 1) läti-liivi kontaktide mõjul kujunenud liivipärase murde ala; 2) Eesti piiri äärsed murrakud; 3) Gulbene ja Alūksne ümbruse murrakud; 4) kreevinite (vadja keele kõnelejate järglaste) ala Zemgales ja 5) Ludza ümbruse murrakud Latgales. Keelekontaktide geolingvistiline uurimine võib kaasa aidata etnilise ajaloo küsimuste lahendamisele.Märksõnad: dialektoloogia, geolingvistika, balti-läänemeresoome keelekontaktid, murdeatlased